Exploring The Impact of User Generated Content, Electronic Word of Mouth (E-WOM), and Brand Trust on Kahf Product Purchase Intent on Social Media - Chairil Mustofa; Ramlah Puji Astuti (Cv. Syntax Corporation Indonesia, 2026)
The rapid development of social media has transformed consumer behavior in accessing information and making purchasing decisions. In the context of digital marketing, User-Generated Content (UGC), Electronic Word of Mouth (eWOM), and brand trust have become important factors influencing consumers’ purchase intentions. Although these variables have been widely studied, limited research has examined their combined effects on purchase intention within regional Indonesian markets, particularly for local brands such as Kahf. This study aimed to analyze the effects of UGC, eWOM, and brand trust on the purchase intention of Kahf products among social media users in Cirebon Regency and Cirebon City. Employing a quantitative approach with a survey method, data were collected from 234 Kahf product users through a Likert-scale questionnaire. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the hypothesized relationships among the constructs. The results indicated that all indicators met the validity and reliability criteria, confirming the adequacy of the measurement model. The R-square value of 0.631 indicated that UGC, eWOM, and brand trust collectively explained 63.1% of the variance in purchase intention, while the remaining variance was explained by other factors. The findings revealed that UGC, eWOM, and brand trust positively influenced consumers’ purchase intentions toward Kahf products. Among these variables, brand trust emerged as the most dominant factor shaping consumers’ purchase intentions. These findings highlight the importance of strengthening brand trust and optimizing user-generated content and digital communication-based marketing strategies to increase consumers’ purchase intentions.